ARK 2018: AWI airborne ultra-wideband radar data over the shear margins at the onset region of the Northeast Greenland Ice Stream (NEGIS) (EGRIP-NOR-2018 Project) - Franke, Steven; Jansen, Daniela; Binder, Tobias; Paden, John D; Dörr, Nils; Gerber, Tamara Annina; Miller, Heinrich; Dahl-Jensen, Dorthe; Helm, Veit; Steinhage, Daniel; Weikusat, Ilka; Wilhelms, Frank; et al. (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWIs multi-channel ultra-wideband radar system (AWI UWB) during the Arctic season of 2018. The radar profiles cover the onset region of the Northeast Greenland Ice Stream (NEGIS). The radar data has been acquired in May 2018 with the Alfred Wegener Institute (AWI) multichannel ultra-wideband radar mounted on the Polar6 aircraft. Radar profiles cover an area of ~24 000 km^2 and extend over the well-defined shear margins of the NEGIS. The survey area is centred at the location of the drill site of the East Greenland Ice-Core Project (EastGRIP) and several radar lines intersect at this location. The survey layout is designed to (1) map the stratigraphic signature of the shear margins with radar profiles aligned perpendicular to ice flow and (2) trace the radar stratigraphy along several flow lines. While we are able to resolve radar reflections in the deep stratigraphy, we cannot fully resolve the steeply inclined reflections at the tightly folded shear margins in the lower part of the ice column. The NEGIS is causing the most significant discrepancies between numerically modelled and observed ice surface velocities. Given the high likelihood of future climate and ocean warming, this extensive data set of new high-resolution radar data in combination with the EastGRIP ice core will be a key contribution to understanding the past and future dynamics of the NEGIS. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: AWI UWB; EastGRIP; EGRIP; Ice core; Ice dynamics; NEGIS; Northeast Greenland Ice Stream; Polar 6; radio-echo sounding; shear margins